2008
DOI: 10.1152/ajprenal.00387.2007
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE-mediated cytotoxicity and apoptosis in ischemic kidney epithelial cells

Abstract: 20-HETE, a metabolite of arachidonic acid, has been implicated as a mediator of free radical formation and tissue death following ischemia-reperfusion (IR) injury in the brain and heart. The present study examined the role of this pathway in a simulated IR renal injury model in vitro. Modified self-inactivating lentiviral vectors were generated to stably overexpress murine Cyp4a12 following transduction into LLC-PK(1) cells (LLC-Cyp4a12). We compared the survival of control and transduced LLC-PK(1) cells follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 44 publications
5
47
0
Order By: Relevance
“…This protection may partially involve the activation of Raf/MEK/ERK and PI3K-Akt pathways, which were shown to be protective against ischemia-reperfusion injury (11). On the contrary, we previously reported that overexpression of a 20-HETE-producing Cyp4a12 isoform was detrimental in LLC-PK 1 cells after an in vitro protocol of ischemia-reperfusion (25). Because the genetically modified LLC-PK 1 cells with the lentiviral vectors promoted constitutively, high-level production of 20-HETE (25), it is likely that there is a differential dose-dependent activation of signaling cascades resulting in the distinct biological functions of this eicosanoid, which may account for the paradoxical contradiction between these two studies.…”
Section: Discussionmentioning
confidence: 96%
“…This protection may partially involve the activation of Raf/MEK/ERK and PI3K-Akt pathways, which were shown to be protective against ischemia-reperfusion injury (11). On the contrary, we previously reported that overexpression of a 20-HETE-producing Cyp4a12 isoform was detrimental in LLC-PK 1 cells after an in vitro protocol of ischemia-reperfusion (25). Because the genetically modified LLC-PK 1 cells with the lentiviral vectors promoted constitutively, high-level production of 20-HETE (25), it is likely that there is a differential dose-dependent activation of signaling cascades resulting in the distinct biological functions of this eicosanoid, which may account for the paradoxical contradiction between these two studies.…”
Section: Discussionmentioning
confidence: 96%
“…23 Cyp4a12 overexpression in renal epithelial cells leads to increased 20-HETE-mediated oxidative stress and cell apoptosis. 24 In addition, high glucose enhances Cyp4a expression and 20-HETE biosynthesis in both podocytes and proximal tubular cells, leading to cell apoptosis and hypertrophy. 15,25 In addition to its direct contribution to kidney cell function, 20-HETE could contribute to renal injury by raising BP via vascular effects.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (34) recently reported antiapoptotic effects of 20-HETE in PA vascular smooth muscle cells, but no mechanisms of protection other than activation of the intrinsic pathway were reported. Nilakantan et al (26) observed enhanced ischemia-reperfusion injury in renal epithelial cells overexpressing CYP4A, an isoform that catalyzes the conversion of arachidonic acid into 20-HETE. These results may be similar to our observations of serum-starved BPAECs exposed to 50 M 20-HETE, which decreased cell numbers.…”
Section: Discussionmentioning
confidence: 99%